Amorphous carbon nanotubes as potent sorbents for removal of a phenolic derivative compound and arsenic: theoretical support of experimental findings. Issue 11 (22nd January 2016) - Bhowmick, P.; Banerjee, D.; Santra, S.; Sen, D.; Das, B.; Chattopadhyay, K. K.
Abstract : Amorphous carbon nanotubes can be uses as potential material for water purification. Abstract : This work depicts the adsorptive removal efficiency of the carcinogenic phenolic derivative compound, resorcinol and highly toxic arsenic(iii ) from water by low temperature, chemically synthesized amorphous carbon nanotubes (a-CNTs). The as prepared a-CNTs were characterized by X-ray diffraction, field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy; Raman spectroscopy and Fourier transform infrared spectroscopy. The a-CNTs were used in order to remove both an organic pollutant as well as a heavy metal like arsenic(iii ) by the process of adsorption. The quantification has been made with the help of UV-Vis spectroscopy. The removal efficiency of a-CNTs for both resorcinol and arsenic(iii ) was analysed by kinetic spectrophotometric study. It is seen that for resorcinol, the maximum possible removal efficiency was 76% within a time period of about 5 hours. Several sorption parameters like contact time, adsorbent dosage and pH were investigated for adsorption of resorcinol. For arsenic(iii ), the removal efficiency was 42%. Also a first principles study has been done and the adsorption of As adatoms on 5–8–5 type double vacancy defects is computationally investigated as a simplified case for As(iii ) atom trapping by a-CNTs. It is seen that the native point defects of a-CNTs bond strongly with As adatoms.